A 5-year comprehensive evaluation of maxillofacial injuries in polytrauma patients at a tertiary hospital - an epidemiological study - Pradeep Muralidhar; Vinod Bandela; Abdul Ahad Ghaffar Khan; Shahi Jahan Shah; Abosofyan Salih Atta Elfadeel; Ram B Basany; Devi Singh Amgoth; Shilpa Param (Medical Journals Sweden, 2024)
Objectives: To report and analyze the pattern of maxillofacial injuries in trauma victims and to define the role of a maxillofacial surgeon in an emergency trauma care team. Materials and methods: Trauma patients reported and reporting to the casualty of a tertiaryhospital with facial injuries and other suspected concomitant injuries in the body were included in this study. The complete medical and radiographic records of each patient were reviewed and data was collected in a standard proforma in this 5-year clinical study (3 year of retrospective and 2 year of prospective study). The complete data related to the facial injuries and associated systemic trauma was recorded and statistical analysis conducted. Results: A total of 18,369 patients with trauma were admitted to the hospital from May 2018 to April 2023. Out of these, 11,277 (61.4%) were males and 7,092 (38.6%) were females. Seventy percent of the reported cases with trauma were in the age group of 14-40 years. The incidence of trauma during the monsoon season was highest (n = 7,927, 43%). The commonest etiological factor leading to trauma was road traffic accident (n = 4,510, 40%). Among facial injuries, the mandibular fractures (n = 1,821, 41%) were predominant. Conclusions: The management of polytrauma patients should be undertaken by a team of specialists which should include a maxillofacial surgeon as facial injuries were common. This data is essential in developing and assessing the preventative strategies aimed at decreasing the frequency of facial and other injuries.